DESA MAWA CARA NEGARA MAWA TATA: DINAMIKA PENGATURAN DESA DALAM SISTEM KETATANEGARAAN INDONESIA - Basuki, Udiyo (UIN Sunan Kalijaga Yogyakarta, 2017)
The history of village arrangements in the state administration system in Indonesia has had ups and downs following the flow of social and political dynamics. In the Dutch and Japanese colonial era, villages were highly neglected. In the old order the existence of legal products that regulate the village actually makes the village eroded and marginalized. In the New Order period the village was regulated separately in Law No. 5 of 1979 which embraced uniformity like a village in Java. This resulted in the existence of indigenous peoples outside Java experiencing tremendous reductions. As the fall of the New Order and replaced by the Reform Order, the existence of villages and indigenous and tribal peoples is reduced to a part of the regency / municipal territory or regency which is incorporated in Law No. 22 of 1999. The next law product is Law No. 6 of 2014, which accommodates the existence of the village and traditional village. The alignment of this Law is in practice worthy of review and testing. This paper describes the development of village settings in the Indonesian state administration system from the beginning of independence until now.Kata kunci: desa mawa cara negara mawa tata, desa, sistem ketatanegaraan, masyarakat adat